Turn-of-Month Evaluations of Liquid Profits and Stock Returns: A Common Explanation for the Monthly and January Effects. - Ogden, Joseph P (Journal of Finance, 1990)
This paper presents and tests a hypothesis that the standardization of payments in the United States at the turn of each calendar month generally induces a surge in stock returns at the turn of each calendar month. The hypothesis also asserts that returns generally will be greater following the month of December and will vary inversely with the stringency of monetary policy. Empirical results using stock index returns for 1969-86 support the hypothesis. This analysis provides an explanation for the previously documented monthly effect in stock returns and a partial explanation for the January effect.